Climatology and first-order composition estimates of mesospheric clouds from Mars Climate Sounder limb spectra - Sefton-Nash, E; Teanby, N; Montabone, L; Irwin, P; Hurley, J; Calcutt, S (2013)
Mesospheric clouds have been previously observed on Mars in a variety of datasets. However, because the clouds are optically thin and most missions have performed surface-focussed nadir sounding, geographic and seasonal coverage is sparse. We present new detections of mesospheric clouds using a limb spectra dataset with global coverage acquired by NASA's Mars Climate Sounder (MCS) aboard Mars Reconnaissance Orbiter. Mesospheric aerosol layers, which can be CO2 ice, water ice or dust clouds, cause high radiances in limb spectra, either by thermal emission or scattering of sunlight. We employ an object recognition and classification algorithm to identify and map aerosol layers in limb spectra acquired between December 2006 and April 2011, covering more than two Mars years. We use data from MCS band A4, to show thermal signatures of day and nightside features, and A6, which is sensitive to short wave IR and visible daytime features only. This large dataset provides several thousand detections of mesospheric clouds, more than an order of magnitude more than in previous studies.Our results show that aerosol layers tend to occur in two distinct regimes. They form in equatorial regions (30°S-30°N) during the aphelion season/northern hemisphere summer (Ls<150°), which is in agreement with previous published observations of mesospheric clouds. During perihelion/dust storm season (Ls>150°) a greater number of features are observed and are distributed in two mid-latitude bands, with a southern hemisphere bias. We observe temporal and longitudinal clustering of cloud occurrence, which we suggest is consistent with a formation mechanism dictated by interaction of broad temperature regimes imposed by global circulation and the propagation to the mesosphere of small-scale dynamics such as gravity waves and thermal tides.Using calculated frost point temperatures and a parameterization based on synthetic spectra we find that aphelion clouds are present in generally cooler conditions and are spectrally more consistent with H2O or CO2 ice. A significant fraction has nearby temperature retrievals that are within a few degrees of the CO2 frost point, indicating a CO2 composition for those clouds. Perihelion season clouds are spectrally most similar to H2O ice and dust aerosols, consistent with temperature retrievals near to the clouds that are 30-80K above the CO2 frost point. © 2012 Elsevier Inc.